(untitled) (Research, Society and Development, 2021)
The environmental crisis has increased over the years, due to several environmental problems, often resulting from the devastating action of man in wanting only economic benefits. The degradation they see occurring in the world has become the main concern of the scientific community, leading it to rethink new strategies to protect the environment in order to guarantee the survival of the global ecosystem and human species. The degradation of natural resources has favored a global approach to environmental problems. With this, several institutions were created to discuss new proposals for preservation, several proposals appeared, and one of these proposals was the introduction of Environmental Education in the school and vocational curriculum. In this perspective, Environmental Education represents a subsidy to strengthen and raise awareness about the importance that the environment has for our survival and that since we have been taking care of the natural resources. Today, the vision on the extraction of natural resources culminating in this increase of degradation and pollution, where it demands the obligation of the organs together with the rulers, but effective in the laws, rigorously punishing the one that degrades the planet, resulting in a new legal mechanism for the protection of natural resources.